Estudo in vivo do papel das quimiocinas e dos receptores de bradicinina, B1 e B2, no recrutamento de leucócitos na microvasculatura cerebral de camundongos com Encefalomielite Autoimune Experimental - Adriana Carvalho dos Santos (2006)
Experimental autoimmune encephalomyelitis (EAE) models multiple sclerosis (MS) and is characterized by marked mononuclear cell influx in the brain.Inflammation leads to demyelinating lesions and disease. Several studies have demonstrated a role for chemokines during EAE. It remains to be determined whether these mediators modulate EAE primarily by mediating leukocyte influx into the CNS or by modifying lymphocyte activation and/or trafficking into lymphoid organs. After induction of EAE with MOG35-55, leukocyte recruitment peaked on day 14 and correlated with symptom onset, TNF-á production and production of CCL2and CCL5. Levels of CXCL-10 and CCL3 were not different from control animals.We demonstrated that leukocyte rolling and adhesion also peaked at day 14. The treatment with anti-CCL2 or anti-CCL5 antibodies just prior to the intravital microscopy prevented leukocyte adhesion, but not rolling. To confirm the role of CCL2 on leukocyte recruitment, we performed different treatments with the mutant protein P8A, described as an inhibitor of CCL2 activity. P8A was able to decrease leukocyte adhesion and ameliorated the clinical course of disease. Our data suggest that induction of leukocyte adhesion to the brain microvasculature is an important mechanism by which CCL2 and CCL5 participate in the pathogenesis ofEAE. Next, we investigated the role of kinins in driving EAE and chemokine production in the brain. The kinins are relevant mediators of inflammation and act through stimulation of two receptor subtypes, B1 and B2. For the present study B1- deficient (B1-/-), B2-deficient (B2- /-) and wild type (WT) mice were used. The incidence of disease was similar in the groups, but the disease in B2-/- mice was less severe. At day 14 after EAE induction, there was a significant decrease in thenumber of adherent leukocytes when compared with WT mice. EAE induced an increase of B1 mRNA in brain tissue and this was partially prevented in B2-/- mice. Expression of CCL5 was suppressed in both B1-/- and B2 -/- mice, but CCL2 expression was only inhibited in B2-/- mice. Altogether, our results suggest that B2 receptors have two major effects in the control of EAE severity: B2 regulates the expression of chemokines, including CCL2 and CCL5, the expression of B1 receptors, and B1-dependent leukocyte influx. Blockade of chemokine action (eg.by using P8A) or production (eg. by using bradykinin antagonists) may represent a valid strategy to prevent leukocyte influx into the brain and disease severity in patients with MS.